2017
DOI: 10.1016/j.ydbio.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-like cells contribute to pax7-dependent skeletal muscle repair in adult zebrafish

Abstract: Satellite cells, also known as muscle stem cells, are responsible for skeletal muscle growth and repair in mammals. Pax7 and Pax3 transcription factors are established satellite cell markers required for muscle development and regeneration, and there is great interest in identifying additional factors that regulate satellite cell proliferation, differentiation, and/or skeletal muscle regeneration. Due to the powerful regenerative capacity of many zebrafish tissues, even in adults, we are exploring the regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 113 publications
(227 reference statements)
6
74
0
Order By: Relevance
“…Primers used to assess efficacy of pnrc2 sbMO injection (Fig S1K–L) are listed in Table S4. upf1, rbfox1l , and rbfox2 sbMO doses were performed according to published methods using doses that gave reproducible phenotypic defects matching published results (Wittkopp et al, 2009; Gallagher et al, 2011; Berberoglu et al, 2017). Embryos were incubated at 28.5°C until 6 hours post fertilization (hpf) and then transferred to 25°C thereafter, except for a subset of rbfox1l/rbfox2 double-injected and uninjected control embryos that were incubated at 28.5°C until 24 hpf and subsequently scored for ability to move.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Primers used to assess efficacy of pnrc2 sbMO injection (Fig S1K–L) are listed in Table S4. upf1, rbfox1l , and rbfox2 sbMO doses were performed according to published methods using doses that gave reproducible phenotypic defects matching published results (Wittkopp et al, 2009; Gallagher et al, 2011; Berberoglu et al, 2017). Embryos were incubated at 28.5°C until 6 hours post fertilization (hpf) and then transferred to 25°C thereafter, except for a subset of rbfox1l/rbfox2 double-injected and uninjected control embryos that were incubated at 28.5°C until 24 hpf and subsequently scored for ability to move.…”
Section: Methodsmentioning
confidence: 89%
“…Interestingly, single upf1 knockdown at published (0.65 ng) or higher doses (2 ng) does not alter her1 mRNA expression, but does induce the expected published phenotypes including neural necrosis and abnormal segment formation (data not shown) (Wittkopp et al, 2009; Anastasaki et al, 2011). As a control, we injected a sub-optimal dose of pnrc2 sbMO (2 ng) with an unrelated MO, rbfox1l sbMO, at the published 6 ng dose (Gallagher et al, 2011; Berberoglu et al, 2017), and observed that her1 mRNA expression is normal (Fig S3), suggesting that her1 misexpression in embryos co-injected with sub-optimal doses of pnrc2 and upf1 sbMOs is a specific effect. Taken together, these results reveal that depletion of Upf1 sensitizes embryos to partial loss of Pnrc2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, the PAX7 orthologue is duplicated in two copies; pax7a and pax7b. pax7a expressing cells act to initiate myofiber formation post-injury, whereas pax7a/b expressing cells are required for myofiber growth [30]. Significant down regulation of both pax7a and b was observed during the larval stage in ddx27 mutant zebrafish.…”
Section: Precocious Skeletal Muscle Differentiation In Ddx27 Deficiencymentioning
confidence: 93%
“…cmet + cells are capable of selfrenewal and contribute to muscle regeneration, suggesting that they are functionally equivalent to mammalian satellite cells (Gurevich et al, 2016). Recent work has also shown that Pax3/7-expressing satellite-like cells in adult zebrafish are essential for the regeneration after muscle injury (Berberoglu et al, 2017). Therefore, pax7 labels multiple MPC populations at different developmental stages in zebrafish: (1) embryonic MPCs in the dermomyotome on the surface of the somite; (2) fiber-associated deep myotomal cells (including cmet + cells) in larval zebrafish; and (3) satellite-like cells in adult zebrafish.…”
Section: Introductionmentioning
confidence: 99%